Spatial Data Science - Bação, Fernando (2020)
Bação, F., Santos, M. Y., & Behnisch, M. (2020). Spatial Data Science. [Editorial]. ISPRS International Journal of Geo-Information, 9(7), 1-5. [428]. https://doi.org/10.3390/ijgi9070428